Estimates of Growth and Acreage Response in Cotton-Producing States of India - Gandhimathy, B. (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The present study investigated the growth and supply response of the major cotton-producing states of India. Three cotton zones, namely the North Zone (Punjab, Haryana, and Rajasthan), the Central Zone (Madhya Pradesh and Gujarat), and the South Zone (Andhra Pradesh, Karnataka, and Tamil Nadu), were taken for analysis. Methodology : Growth analysis, component analysis, and adaptive expectation models were applied to time series data spanning 25 years, from 1998–1999 to 2022–2023, subdivided into two phases from 1998–1999 to 2010–2011 and from 2010–2011 to 2022–2023. Microsoft Excel and EViews’ 12th version software were used in this study. Findings : The study revealed that Gujarat, Karnataka, and Rajasthan had relatively higher growth rates, while Punjab and Andhra Pradesh had the lowest growth rates. Cultivation and labor costs were much higher in Andhra Pradesh and Punjab; particularly, Tamil Nadu’s cost of cultivation was doubled compared to Haryana. The study revealed that every 100% increase in lagged farm price increased the acreage under cultivation at 21% in the short run and 55% in the long run in Rajasthan, which was the highest among the cotton-producing states. Every 100% increase in farm prices reduced cotton cultivation by 9% and 12% in Punjab and Andhra Pradesh, respectively, in the short run, and by 73% and 53% in the long run. Hence, perverse supply was found in these states. This implied that the price increase was sufficient to cover the cost of production, reflecting changes in farmers’ decisions regarding the allocation of land to cotton. Practical Implications : Cost variations and wage disparity appeared across states. When BT cotton was introduced in 2002, phenomenal growth was witnessed; now, there is a need to upgrade new varieties. Minimum support prices should be increased, as price has a significant impact on the growth of cotton growers. The minimum support prices will be favorable only to the low-cost cultivating states and vice versa. Increase in price was not sufficient in Punjab, Andhra Pradesh, and Madhya Pradesh, which need to be focused upon. Originality : The study comprehensively analyzed the growth of the cotton crop across the Indian states. It analyzed the impact of cost and price variations among the states and how these variations reflected on the farming of the cotton crop.